Pengaruh Modal Kerja dan Penjualan Terhadap Laba Bersih pada UMKM di Telukjambe Timur Karawang - Deka Putri Lestari; Uus MD Fadli (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The important role of MSMEs in the Indonesian economy, especially in providing employment and income for low-income people. This research aims to examine the influence of working capital and sales on net profit in MSMEs in Telukjambe Timur Karawang. The purpose of this research is to find out how much influence working capital and sales have on net profit. The method used is descriptive quantitative with a sample of 100 MSME entrepreneurs selected by purposive sampling. Primary data was obtained through questionnaires and analyzed using multiple regression. Research findings show that working capital and sales simultaneously do not have a significant effect on net profit. The implications of this research indicate the need for more efficient working capital management and more effective sales increase strategies to increase net profits in MSMEs.